Dermal nerve fibre and mast cell density, and proximity of mast cells to nerve fibres in the skin of patients with complex regional pain syndrome. Issue 10 (October 2018) - Morellini, Natalie; Finch, Philip M.; Goebel, Andreas; Drummond, Peter D.
Abstract : Abstract: An interaction between cutaneous nerves and mast cells may contribute to pain in complex regional pain syndrome (CRPS). To explore this, we investigated the density of dermal nerve fibres, and the density and proximity of mast cells to nerve fibres, in skin biopsies obtained from the affected and unaffected limbs of 57 patients with CRPS and 28 site-matched healthy controls. The percentage of the dermis stained by the pan-neuronal marker protein gene-product 9.5 was lower in the affected limb of patients than in controls (0.12 ± 0.01% vs 0.22 ± 0.04%, P < 0.05), indicating a reduction in dermal nerve fibre density. This parameter did not correlate with CRPS duration. However, it was lower in the affected than unaffected limb of patients with warm CRPS. Dermal mast cell numbers were similar in patients and controls, but the percentage of mast cells less than 5 µm from nerve fibres was significantly lower in the affected and unaffected limbs of patients than in controls (16.8 ± 1.7%, 16.5 ± 1.7%, and 31.4 ± 2.3% respectively, P < 0.05). We confirm previous findings of a mild neuropathy in CRPS. Our findings suggest that this either develops very early after injury or precedes CRPS onset. Loss of dermal nerve fibres in CRPS might result in loss of chemotactic signals, thus halting mast cell migration toward surviving nerve fibres. Failure of normal nerve fibre–mast cell interactions could contribute to the pathophysiology of CRPS. Abstract : Supplemental Digital Content is Available in the Text.Loss of dermal nerve fibres in complex regional pain syndrome might disrupt neural–mast cell interactions, thereby delaying tissue repair and contributing to chronic inflammation.